THE INFLUENCE OF IBN QAYYIM AL-JAUZIYAH IN THE REALITY OF MUSLIMS TODAY - Samsidar Jamaluddin; Kurniati Kurniati; Misbahuddin Misbahuddin (International Journal of Social Science, 2022)
Ibn Qayyim invites and calls on Muslims to ijtihad and leave taklid, Ibn Qayyim al-Jauziyah is a scholar who is very persistent in fighting blind taklid and calling for freedom of thought, but still clinging to the main points of Islamic teachings and the creed of the Salaf. In Ibn Qayyim's view, ijtihad must develop in accordance with the development of situations and conditions in various places and times. Therefore he put forward a rule: Fi taghayyir al-fatawa wa ikhtilafiha bi hasbi taghayyir al-azminah wa al-amkinah wa al-ahwal wa al-niyat wa al-'awa'id. According to him, an important factor in formulating legal provisions or legal stipulations must be related to five things, namely al-azminah (the situation of the times), al-amkinah (the situation of the place), al-ahwal (the circumstances), al-niyat (the cause of desires), and al-awa'id (customs). All of this affects the development of law, so that Islamic law can truly be lived as a law that is rahmatan lil 'alamin, able to answer the challenges of changing social dynamics of society. Thus Islamic law remains suitable for all times and places.